The Relationship of Knowledge, Attitude and Behavior Early Detection of Cervic Cancer In Midwifes In Puskesmas Surabaya - Fransisca Wiga Alda Maretha; Pungky Mulawardhana; Reny I’tishom (Syntax Corporation, 2022)
Background: Cervical cancer is the second most common type of cancer after breast cancer. Cervical cancer is a special concern of the government to support the success of the SDGs (Sustainable Development Goals). The government established a cervical cancer prevention program for 2015-2019 in collaboration with public health centers and local governments in detecting cervical cancer early in the community. Midwives have an important role in tackling cervical cancer, but there are still few studies in Indonesia that discuss the relationship between knowledge of midwives in attitudes and behavior to carry out early detection of cervical cancer for themselves. The purpose of this study was to determine the relationship between knowledge, attitudes, and behavior of early detection of cervical cancer in midwives at Puskesmas Surabaya. Methods: This research method is observational analytic with the cross-sectional approach. The number of samples is 94 with the random sampling technique. The independent variables are knowledge and attitudes and the dependent variable is behavior. The instrument used is a questionnaire. Using chi-square and fisher test. Results: There were 72 people (78.7%) who had good knowledge at the Surabaya Public Health Center, 52 people (55.3%) with a good attitude, and 49 people (52.1%). The results of the statistical test of knowledge with behavior p = 0.221 (p> 0.05), knowledge with attitude p = 0.039 (p <0.05), and behavior with attitude p = 0.042 (p <0.05). Conclusion: There is a relationship between knowledge of cervical cancer and attitudes towards early detection of cervical cancer, there is a relationship between attitudes towards early detection of cervical cancer and behavior for early detection of cervical cancer and there is no relationship between knowledge of cervical cancer and behavior of early detection of cervical cancer.